Hegemonic leadership: a mirror of dominant masculinity in Brazil - Ramos Filho, Augusto Ferreira (2025)
This research aimed to analyze the iconographies of masculinities in Brazil. The qualitative and exploratory research sought to understand the words and images that were linked to masculinities. The research was carried out using an electronic form where the subjects could freely answer which three words and symbols best describe masculinity. A total of 418 responses were retrieved. A total of 1229 words and 1152 symbols were collected, which were fragmented into categories. This research analyzed the categories described as emotional, physical and social. The research identified that male hegemony influences not only how leadership is exercised, but how gender asymmetry is still significant today.